Theoretical aspects of teachers’ training and analysis of development programs quality in institutions of higher pedagogical education - Ponomarova, Galina; Kharkivska, Alla; Molchaniuk, Olga (My University, 2018)
У статті розглянуто та охарактеризовано основні наукові підходи до системи підготовки вчителів, показані їх особливості та вплив на формування професійної складової особистості студента, проаналізовані критерії оцінювання якості програм інноваційного розвитку закладу вищої педагогічної освіти як складову системи управління інноваційним розвитком закладу вищої педагогічної освіти. The article discusses and describes the main scientific approaches to the training of teachers, shows their features and influence in shaping the professional component of the student’s personality, analyzes the evaluation criteria as innovative development programs as part of institute management system development of innovative institute of higher pedagogical education.
Ponomarova G. Theoretical aspects of teachers’ training and analysis of development programs quality in institutions of higher pedagogical education / G. Ponomarova, А. Kharkivska, O. Molchaniuk // Проектування життєвої компетентності учнівської молоді : колективна монографія / за наук.ред. проф.. Кузьміної О.В. – Hameln: InterGING, 2018. –С. 99–114.
Keywords: компетентнісний підхід, особистісно-орієнтований підхід, аксіологічний підхід, підготовка вчителів, інноваційний розвиток, критерії оцінювання, програма, заклад вищої педагогічної освіти.; competence approach, personality-based approach, axiological approach, teachers’ training, innovative development, evaluation criteria, program, institute of higher pedagogical education.